2005
DOI: 10.1038/sj.gt.3302538
|View full text |Cite
|
Sign up to set email alerts
|

A novel adenoviral vector which mediates hypoxia-inducible gene expression selectively in neurons

Abstract: Selective gene expression in neurons is still a challenge. We have developed several expression vectors using a combination of neuron restrictive silencer elements (NRSEs), hypoxia responsive elements (HREs) and CMV minimal promoter (CMVmp). These elements were packaged into replication defective adenovirus to target gene expression selectively in neurons in a hypoxia-regulated manner. Neuronal selectivity and responsiveness to hypoxia of these novel constructs were determined empirically in both neural cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…In total, 10 lg DNA was used per transfection assay with the Lipofectamine 2000 transfection reagent (Invitrogen, Carlsbad, CA, USA). Briefly, cortical neurons plated in a 24-well plate were transfected at 7 days in vitro (DIV) as previously described (Huang et al 2005). The transfection efficiency is about 10% of the total number of cells in the dish.…”
Section: Plasmid Preparation and Transfectionmentioning
confidence: 99%
“…In total, 10 lg DNA was used per transfection assay with the Lipofectamine 2000 transfection reagent (Invitrogen, Carlsbad, CA, USA). Briefly, cortical neurons plated in a 24-well plate were transfected at 7 days in vitro (DIV) as previously described (Huang et al 2005). The transfection efficiency is about 10% of the total number of cells in the dish.…”
Section: Plasmid Preparation and Transfectionmentioning
confidence: 99%
“…Different copies of HRE can decrease the basal promoter activity under normoxic conditions. As shown in a previous study, the 5HRE-3NRSE regulator cassette decreased the basal CMVmp activity by approximately 50-97% in comparison with that of the CMV construct in cultured cells under normoxic conditions (19). Moreover, almost no humanized Renilla GFP (hrGFP) expression occurred in the PC12 cells infected by Ad-5HRE-hrGFP under normoxic conditions (20).…”
Section: Discussionmentioning
confidence: 92%
“…First, HRE can decrease the basal promoter activity under normoxic conditions. It has been reported that a 5HRE-3NRSE regulator cassette decreased the basal cytomegalovirus minimal promoter (CMVmp) activity nearly by 50% and up to 97% in comparison with that of the CMVmp construct in cultured cells under normoxic conditions (Huang et al, 2005). Furthermore, almost no hrGFP expression occurred in PC12 cells infected by Ad-5HRE-hrGFP under normoxic conditions (Hu et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…To assess the potential non-specific effects of the vector, reporter genes are commonly used, such as green fluorescent protein (GFP), b-Galactosidase (LacZ) and luciferase (Huang et al, 2005;Shen et al, 2006;Shi et al, 2009). We used EGFP as a system as well as a control for non-specific effects.…”
Section: Discussionmentioning
confidence: 99%